THE INFLUENCE OF PRODUCT QUALITY DIMENSIONS ON CUSTOMER SATISFACTION RAWON GRAGAL TYPICAL TRENGGALEK EAST JAVA - Rohmad Prio Santoso (Media Inovasi Pendidikan dan Publikasi, 2024)
This study aims to determine how much the influence of product quality dimensions related to eating products contributes to customer satisfaction in Trenggalek Rawon Gragal specialty foods. This research data collection technique uses a questionnaire using purposive sampling technique with a sample size of 80 respondents. The results showed that of the four dimensions of product quality consisting of freshness, presentation, taste, and innovative food, each has a significant contribution to the customer satisfaction of typical Trenggalek Rawon Gragal food lovers. Of the four dimensions of product quality, the presentation dimension has the greatest influence, this is because Rawon Gragal connoisseurs prefer the presentation method which has the highest score and is followed by food portions. Suggestions for further research need to consider or update indicators that are relevant to the conditions and objects of research.